2014
DOI: 10.3126/narj.v9i0.11640
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Production under Long-term Application of Inorganic and Organic Fertilizers in Rice-Wheat System under Rainfed Conditions

Abstract: Under rainfed rice-wheat cropping system, experiments were conducted on wheat variety Annapurna-2 from 1998 to 2002 to study the effect of continuous application of inorganic and organic fertilizers in longer run on wheat production and soil properties in alluvial soil of Khumaltar, Lalitpur at 1365 msal. Eleven different fertilizers combinations comprised of inorganic  and organic fertilizers were used. The results of the five-year experiment  indicate that the applications of optimal level of inorganic ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The increasing dose of N result the linear increment in spike length in both years for all pipeline varieties. These results are in conformity with those of (Rai and Khadka 2009) who observed maximum spike length under fertilization of 100 kg N ha -1 as compared to control and 50 kg N ha -1 in their long term experiment in Khumaltar. Higher test weight with increasing N levels might be due to supply of more N and higher production of photosynthates (Naseri et al 2010) that showed linearly increased test weight due to increasing levels of N application (Figure 4).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The increasing dose of N result the linear increment in spike length in both years for all pipeline varieties. These results are in conformity with those of (Rai and Khadka 2009) who observed maximum spike length under fertilization of 100 kg N ha -1 as compared to control and 50 kg N ha -1 in their long term experiment in Khumaltar. Higher test weight with increasing N levels might be due to supply of more N and higher production of photosynthates (Naseri et al 2010) that showed linearly increased test weight due to increasing levels of N application (Figure 4).…”
Section: Discussionsupporting
confidence: 80%
“…The effectiveness of N depends on many factors mainly the term of N applications and the variety (Podolska 2014). There are several studies on the use of N fertilizers and wheat production in Nepal (Rai and Khadka 2009, NWRP 2012, Bhattari et al 2015. However, in present work we elucidate the response of wheat genotypes to different levels of N fertilizers applied for the selection of most promising genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Panicle length demonstrated an upward trend with rising nitrogen dose, notably in plots managed using UDP, GS, LCC, and PCU techniques. Similarly, Rai and Khadka (2009) documented a linear spike length increase in response to higher nitrogen dose. Another component is grain yield from the RDF treatment, which was statistically on par with LCC and SPAD, despite these treatments utilizing less nitrogen than RDF.…”
Section: Discussionmentioning
confidence: 88%
“…This has compelled people to introduce high yielding crop varieties. With the introduction of such high yielding crop varieties, the use of chemical fertilizers has also been increased (Rai and Khadka 2009). Inadequate supply of nitrogen (N) fertilizers can limit the potential productivity of the crop and excessive N causes environmental pollution and economic losses (Rahman et al 2021).…”
Section: Introductionmentioning
confidence: 99%